(9y+1)⋅(7y−4)=(63y−5)(y+1) Решите уравнение

(9y+1)⋅(7y−4)=(63y−5)(y+1) Решите уравнение
Гость
Ответ(ы) на вопрос:
Гость
(9y+1)⋅(7y−4)=(63y−5)(y+1) 63у²+7у-36у-4=63у²+63у-5у-5 63у²+7у-36у-63у²-63у+5у=4-5 -87у=-1 у=[latex] \frac{1}{87} [/latex]
Гость
63y-36+7y-4=63y^{2}+63y-5y-5=0 63y^{2}+63y-5y-5-63y+36-7y+4=0 (+63y) и (-63y) сокращаем 63y^{2}-5y-5+36-7y+4=0 63y^{2}-12y+35=0 1) D=в^{2}-4ac= (-12)^{2} - 4*63*35= 144-8820 2)[latex] x_{1.2}= \frac{-B}{2a}= \frac{12}{2*63}= \frac{12}{126}= 0.09[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы